A Review of Entrepreneurship Education in Teacher Education (Malaysian Journal of Learning and Instruction, 2018)
Purpose â€“ The aim of this study is to examine research conducted on entrepreneurship education in teacher education. Methodology â€“ A thematic analysis was used in this study that outlines the similarities and differences in the studies conducted on entrepreneurship education in teacher education. Findings â€“ The purpose of the studies in question was mostly to discuss curriculum, teacher training, economy and unemployment, entrepreneurial characteristics and the importance of teachers. The studies mostly aimed to examine the attitudes, perceptions and views of students, teachers or other educators regarding entrepreneurship education. There were a lot of study results highlighting the importance of entrepreneurship in teacher training. The biggest emphasis was laid upon methods, techniques, models or strategies used in entrepreneurship education. The recommendations put forward in the studies reviewed mostly concerned a basic level of education. Many of these studies stated that in-service training should be given to teachers at the basic education level with regard to entrepreneurship education. Significance â€“ This study contributes to the literature in three different ways. Firstly, by presenting the current status of the studies on entrepreneurship education as a contemporary subject in teacher education. Secondly, it sheds light on the studies that will be conducted in the future as to how to approach the subject of entrepreneurship education in teacher education. Thirdly, by investigating studies that draw attention to entrepreneurship education in teacher education, it provides a better understanding of the importance of entrepreneurship education.